Ethical-legal profile of compulsory and optional vaccinations - Bompiani, Adriano (Medicina e Morale, 1991)
The author deals with the theme of compulsory and optional vaccinations under the ethical and legal profile. In particular, after mentioning the difference between the ethical and the legal aspects, he points out the following aspects: 1) the analysis of the ethical factors inherent in the Health Authorities' decisions as to whether the vaccinations should be compulsory or optional; 2) evaluation of the ethical factors which should guide the attitude of the citizen when faced with the request for prevention health treatments, whether complusory or optional; 3) moral freedom of the parent and of the child; 4) intrinsic characteristics of the licitness of the treatment (safety of the results, harmlessness of the vaccine from the technical point of view, etc).